Sustainability Literacy in Families: A Review of the Literature on Values, Understanding, and Practices - Ismayanti Pratiwi; Susri Adeni; Machyudin Agung Harahap (JURNAL PENDIDIKAN DAN KELUARGA, 2025)
This study aims to examine sustainability literacy within families using a Systematic Literature Review (SLR) approach, focusing on three key dimensions: values, understanding, and sustainable practices. Following the PRISMA protocol, 23 scholarly articles published between 2016 and 2025 were analyzed thematically. The findings indicate that sustainability values—such as social responsibility, simplicity, and ecological justice—are transmitted intergenerationally through role modeling and family interactions. Sustainability understanding is shaped through discussion, communication, and shared learning experiences, which enhance critical awareness and reflective thinking on environmental issues. Sustainable practices in households manifest in energy management, conscious consumption, waste reduction, and green financial behavior. These three dimensions are interconnected and form an intergenerational cycle of sustainability education. This review highlights the strategic role of the family as an agent of transformation toward environmentally conscious societies. The findings also suggest future research opportunities related to family-based sustainability communication and time management within sustainable living practices.